Nanostructural origin of semiconductivity and large magnetoresistance in epitaxial NiCo2O4/Al2O3 thin films. (19th March 2018) - Zhen, Congmian; Zhang, XiaoZhe; Wei, Wengang; Guo, Wenzhe; Pant, Ankit; Xu, Xiaoshan; Shen, Jian; Ma, Li; Hou, Denglu
Abstract: Despite low resistivity ( 1 mΩ cm), metallic electrical transport has not been commonly observed in inverse spinel NiCo2 O4, except in certain epitaxial thin films. Previous studies have stressed the effect of valence mixing and the degree of spinel inversion on the electrical conduction of NiCo2 O4 films. In this work, we studied the effect of nanostructural disorder by comparing the NiCo2 O4 epitaxial films grown on MgAl2 O4 (1 1 1) and on Al2 O3 (0 0 1) substrates. Although the optimal growth conditions are similar for the NiCo2 O4 (1 1 1)/MgAl2 O4 (1 1 1) and the NiCo2 O4 (1 1 1)/Al2 O3 (0 0 1) films, they show metallic and semiconducting electrical transport, respectively. Post-growth annealing decreases the resistivity of NiCo2 O4 (1 1 1)/Al2 O3 (0 0 1) films, but the annealed films are still semiconducting. While the semiconductivity and the large magnetoresistance in NiCo2 O4 (1 1 1)/Al2 O3 (0 0 1) films cannot be accounted for in terms of non-optimal valence mixing and spinel inversion, the presence of anti-phase boundaries between nano-sized crystallites, generated by the structural mismatch between NiCo2 O4 and Al2 O3, may explain all the experimental observations in this work. These results reveal nanostructural disorder as being another key factor for controlling the electrical transport of NiCo2 O4, with potentially large magnetoresistance for spintronics applications.